2001
DOI: 10.1063/1.1331320
|View full text |Cite
|
Sign up to set email alerts
|

Many-body effects and matrix inversion in low-Reynolds-number hydrodynamics

Abstract: It is shown that the method of reflections in resistance form ͑with truncated multipoles͒ is one of many possible iterative methods to obtain the inverse of the mobility matrix ͑with the same truncation͒ in low-Reynolds-number hydrodynamics. Although the method of reflections in the mobility form is guaranteed to converge, it is found that in the resistance form the method may fail to converge. This breakdown is overcome by conjugate-gradient-type iterative methods, and the implications of the iterative method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…The subject was examined by Ichiki and Brady [26], who showed that the method of reflections is mathematically equivalent to the inversion of a mobility problem performed by the Jacobi method, which is not unconditionally stable. However, the implementation of the method of reflections by these authors, which is based on truncated multipoles, is different from the one presented here and was found to be less stable.…”
Section: Evaluation Of the Hydrodynamic Forcementioning
confidence: 99%
“…The subject was examined by Ichiki and Brady [26], who showed that the method of reflections is mathematically equivalent to the inversion of a mobility problem performed by the Jacobi method, which is not unconditionally stable. However, the implementation of the method of reflections by these authors, which is based on truncated multipoles, is different from the one presented here and was found to be less stable.…”
Section: Evaluation Of the Hydrodynamic Forcementioning
confidence: 99%
“…For a fixed geometry, as in the lattice calculations described in § 3, the relaxation parameter has no effect. As suggested by Ichiki & Brady (2001), the breakdown of the method of reflections can also be overcome by the use of a conjugate-gradient-type iterative method. The generalized minimum residual method (GMRES) was used here, and it was found that very accurate results can always be obtained with very few iterations.…”
Section: Force Lawsmentioning
confidence: 99%
“…Determining the forces is the resistance formulation of the problem -for a given configuration of particles and particle velocities, the particle forces and force moments are calculated. It has recently been shown (Ichiki & Brady 2001) that the method of reflections (which corresponds to the simplest iterative scheme for the inversion of the mobility matrix) can be divergent when more than two particles are present.…”
Section: Force Lawsmentioning
confidence: 99%
“…I is unit tensor. Ichiki and Brady [16] have shown the equivalence between the method of reflections and inversion of mobility matrix.…”
Section: Accelerated Stokesian Dynamics Without Adjustable Parametermentioning
confidence: 98%
“…This is the essence of reflection method. The method of reflections of the force version can be expressed in a matrix form as follows [16] …”
Section: Accelerated Stokesian Dynamics Without Adjustable Parametermentioning
confidence: 99%